EFEK MODERASI KEBIJAKAN DIVIDEN DAN KEPEMILIKAN INSTITUSIONAL PADA HUBUNGAN TAX AVOIDANCE DAN NILAI PERUSAHAAN: (Studi Empiris pada Perusahaan Indeks LQ45 periode 2015-2019) - Wirianto, Dhani; Helmi Yazid; Agus Sholikhan Yulianto (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This study was conducted to review the relationship between firm value and tax behavior byincluding dividend policy and institutional ownership as moderating variables. The object ofresearch is the companies that are members of the LQ45 index for the 2015-2019 period witha total sample of 9 companies. Data analysis used descriptive analysis and verificationanalysis through the Moderated Regression Analysis (MRA) test. The results obtained thattax avoidance has no effect on firm value, dividend policy is proven to be a moderatingvariable that can weaken the relationship between tax avoidance and firm value, andinstitutional ownership cannot provide a moderating effect on the relationship between taxavoidance and firm value. This study suggests that LQ45 index companies increase theportion of the dividend policy given, so as to increase investor interest in the company'sshares, in addition to looking at the value of their profits. Further research is suggested toreturn to using institutional ownership as a moderating variable because in this study it wasfound to have the potential to be a moderating on firm value.